Processes and materialization of urban agriculture as activism in the city of São Paulo: the case of the Corujas Community Garden - Nagib, Gustavo (Pontifícia Universidade Católica de São Paulo, 2019)
This article presents urban agriculture as activism in the city of São Paulo based on the consolidation of a network called "Hortelões Urbanos" in 2011, which contributed to the materialization of the first community garden in 2012: the Corujas Community Garden. To conduct this case study, we used the methodology of action research and focused on the historical process that led to the materialization of that community garden, examining the socio-spatial transformations of both the public square and the neighborhoods where it is located. This model of local activism has stimulated legislative and cultural changes throughout the city, and its analysis leads to new reflections on urban space and updates the debate about the right to the city.